2023
DOI: 10.3389/fpsyt.2023.1182345
|View full text |Cite
|
Sign up to set email alerts
|

Role of FKBP5 and its genetic mutations in stress-induced psychiatric disorders: an opportunity for drug discovery

Mahdi Malekpour,
Dorsa Shekouh,
Mohammad Ebrahim Safavinia
et al.

Abstract: Stress-induced mental health disorders are affecting many people around the world. However, effective drug therapy for curing psychiatric diseases does not occur sufficiently. Many neurotransmitters, hormones, and mechanisms are essential in regulating the body's stress response. One of the most critical components of the stress response system is the hypothalamus-pituitary-adrenal (HPA) axis. The FKBP prolyl isomerase 51 (FKBP51) protein is one of the main negative regulators of the HPA axis. FKBP51 negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 219 publications
0
5
0
2
Order By: Relevance
“…Peroxisome proliferator-activated receptor gamma (PPARG) is a transcription factor located on 3p25.2 [ 31 ] that is involved in regulating macrophage polarization, lipid metabolism and inflammation [ 32 ]. FK506-binding protein 5 (FKBP5) is situated on 6p21.31[ 33 ], which binds to glucocorticoid receptors, playing a critical role in regulating cellular stress response, metabolism, and immune response [ 34 ]. qRT-PCR results showed that lower and higher mRNA expression of PPARG in RA and CAD tissues compared with their normal tissues, which is consistent with DEGs results from bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor gamma (PPARG) is a transcription factor located on 3p25.2 [ 31 ] that is involved in regulating macrophage polarization, lipid metabolism and inflammation [ 32 ]. FK506-binding protein 5 (FKBP5) is situated on 6p21.31[ 33 ], which binds to glucocorticoid receptors, playing a critical role in regulating cellular stress response, metabolism, and immune response [ 34 ]. qRT-PCR results showed that lower and higher mRNA expression of PPARG in RA and CAD tissues compared with their normal tissues, which is consistent with DEGs results from bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa neurotransmitter, hormon sangat penting dalam respon tubuh terhadap stress. Salah satu komponen penting dalam tubuh kita yang memberikan respon tersebut adalah hipotalamus pituitary adrena (HPA) (Malekpour et al, 2023). FK506-binding protein 2 (KBP2) adalah gen pengkode protein yang ditemukan pada spesies manusia.…”
Section: Fkbp2unclassified
“…Namun, berdasarkan riset yang lain mengemukakan bahwa gen FKBP51 merupakan yang berpengaruh terhadap respon kejiwaan ini. Oleh karena itu, temuan dari penelitian ini menetapkan pentingnya FKBP51 sebagai target terapi yang menjanjikan untuk stres yang diinduksi karena gangguan kejiwaan (Malekpour et al, 2023). Dalam studi yang lain ditemukan pada FKBP5 dapat berhubungan dengan stres dan penyalahgunaan atau ketergantungan ganja (Misiak et al, 2017).…”
Section: Fkbp2unclassified
“…However, following ELS exposure, activated GRs, due to elevated levels of GCs, increase the transcription of the co-chaperonine FKBP Prolyl Isomerase 5 ( FKBP5 ), which represses GR activity by limiting the translocation of the receptor complex into the nucleus and by inhibiting the transcription of its target genes [ 8 , 9 ]. Specifically, preclinical studies suggest that an increased expression of FKBP5 in several brain regions is associated with decreased stress coping, increased stress responsiveness, increased anxiety, and impaired fear extinction, all traits associated with vulnerability to psychiatric disorders (see for review [ 4 , 10 ]). In line with preclinical findings, post-mortem human brain studies also report elevated FKBP5 mRNA levels in cortical regions across different psychiatric disorders, including depression [ 11 ], post-traumatic stress disorder (PTSD) [ 12 ], and schizophrenia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%